Effectiveness of a workplace intervention reducing psychosocial stressors at work on blood pressure and hypertension. (26th April 2021) - Trudel, Xavier; Gilbert-Ouimet, Mahée; Vézina, Michel; Talbot, Denis; Mâsse, Benoît; Milot, Alain; Brisson, Chantal
Abstract : Objectives: To assess the effectiveness of a workplace intervention reducing psychosocial stressors at work in lowering blood pressure and hypertension prevalence. Methods: The study design was a quasi-experimental pre–post study with an intervention group and a control group. Post-intervention measurements were collected 6 and 36 months after the midpoint of the intervention. Participants were all white-collar workers employed in three public organisations. At baseline, the intervention and the control groups were composed of 1088 and 1068 workers, respectively. The intervention was designed to reduce psychosocial stressors at work by implementing organisational changes. Adjusted changes in ambulatory blood pressure and hypertension prevalence were examined. Results: Blood pressure and hypertension significantly decreased in the intervention group while no change was observed in the control group. The differential decrease in systolic blood pressure between the intervention and the control group was 2.0 mm Hg (95% CI: −3.0 to –1.0). The prevalence of hypertension decreased in the intervention group, when compared with the control group (prevalence ratio: 0.85 (95% CI: 0.74 to 0.98)). Conclusions: Findings suggest that psychosocial stressors at work are relevant targets for the primary prevention of hypertension. At the population level, systolic blood pressure reductions such as those observed in the present study could prevent a significant number of premature deaths and disabling strokes.